1993
DOI: 10.1021/ac00071a008
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast attachment monitored with a quartz crystal microbalance

Abstract: A quartz crystal microbalance is used in aqueous solutions to monitor the rate of attachment of osteoblasts, bone-forming cells, to the surface of the crystal. Changes in resonant frequency of the crystal are measured for various surface coverages by osteoblasts. Crystal surface coverages are determined by digital image processing of scanning electron micrographs. A linear relationship is established between the surface coverages and the changes in resonant frequency of the crystal. The osteoblasts are observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 10 publications
3
91
0
3
Order By: Relevance
“…This behavior indicates that the process is not controlled by diffusion but the adsorption rate of osteoblasts on the Ti surface. Redepenning et al (1993) observed similar behavior for a single layer of osteoblasts using the Kanazawa equation (Kanazawa and Gordon, 1985). If these results are compared with the adhesion kinetics for other cellular lines one concludes that, in this case, the kinetics is very slow, since during the testing time there was no observed increase in the frequency due to stiffening of the attached cells (Galli Marxer et al, 2003).…”
Section: Resultssupporting
confidence: 54%
“…This behavior indicates that the process is not controlled by diffusion but the adsorption rate of osteoblasts on the Ti surface. Redepenning et al (1993) observed similar behavior for a single layer of osteoblasts using the Kanazawa equation (Kanazawa and Gordon, 1985). If these results are compared with the adhesion kinetics for other cellular lines one concludes that, in this case, the kinetics is very slow, since during the testing time there was no observed increase in the frequency due to stiffening of the attached cells (Galli Marxer et al, 2003).…”
Section: Resultssupporting
confidence: 54%
“…The decay of the signal may be influenced by adhesion of bacteria to the surface. However, the frequency shift is related to mass loading on the crystal surface, but when monitoring is done in liquid, the frequency also depends on the viscosity and density of the liquid in contact with the resonator (25,40) and is not necessarily directly proportional to the change in ƒ (3,7,11,19,29,37). The frequency shift is proportional to the attached mass only when the mass is rigid and tightly coupled to the surface (20), which is not the case for bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the removal of material from surfaces can be monitored [155][156][157]. Monitoring the rate of surface accumulation of particulates, including cells [158] and atmospheric [159,160] and cosmic dust [161], has also been demonstrated.…”
Section: Materials Deposition and Removalmentioning
confidence: 99%